Procalcitonin and C-reactive protein-based decision tree model for distinguishing PFAPA flares from acute infections - Kraszewska-Głomba, Barbara (Bosn J Basic Med Sci, 2016)
As no specific laboratory test has been identified, PFAPA (periodic fever, aphthous stomatitis, pharyngitis and cervical adenitis) remains a diagnosis of exclusion. We searched for a practical use of procalcitonin (PCT) and C-reactive protein (CRP) in distinguishing PFAPA attacks from acute bacterial and viral infections. Levels of PCT and CRP were measured in 38 patients with PFAPA and 81 children diagnosed with an acute bacterial (n=42) or viral (n=39) infection. Statistical analysis with the use of the C4.5 algorithm resulted in the following decision tree: viral infection if CRP≤19.1 mg/L; otherwise for cases with CRP>19.1 mg/L: bacterial infection if PCT>0.65ng/mL, PFAPA if PCT≤0.65 ng/mL. The model was tested using a 10-fold cross validation and in an independent test cohort (n=30), the rule’s overall accuracy was 76.4% and 90% respectively. Although limited by a small sample size, the obtained decision tree might present a potential diagnostic tool for distinguishing PFAPA flares from acute infections when interpreted cautiously and with reference to the clinical context.